Imaging the Microcirculation. (July 2016) - Murray, Andrea; Dinsdale, Graham
Abstract: This special issue includes the abstracts from, and three reviews by invited speakers at, the British Microcirculation Society's Annual Meeting in 2015. The reviews cover topics from the meeting symposium of "Imaging the Microcirculation" and discuss noninvasive methods of visualizing and measuring the microvasculature's structure and function.